Molecular characterization of carbapenem-resistant Acinetobacter baumannii using WGS revealed missed transmission events in Germany from 2012-15 - Eigenbrod, Tatjana; Reuter, Sandra; Gross, Andrea; Kocer, Kaan; Günther, Frank; Zimmermann, Stefan; Heeg, Klaus; Mutters, Nico T.; Nurjadi, Dennis (The journal of antimicrobial chemotherapy, 2019)
Background: Infection and colonization with multi-resistant Acinetobacter baumannii causes therapeutic and economic problems in the nosocomial setting. Due to the sensitivity issue of screening schemes for A. baumannii, it is difficult to implement adequate transmission prevention measures. The high discriminatory power of WGS for transmission-chain analysis provides us with the necessary tool to study and identify transmission events. We retrospectively sequenced and analysed 39 A. baumannii isolates from 2012–15 to search for possible missed transmission events. Methods: Molecular typing by WGS was performed for non-repetitive (n=39) carbapenem-resistant A. baumannii. Retrospective assessment of patient records was performed to investigate and confirm possible transmission events. Results: Between July 2012 and September 2015, A. baumannii was isolated from 268 patients, of which 16% (42/268) were carbapenem resistant. Thirty-nine of these isolates were recoverable and sequenced. Fifteen percent (6/39) of these were resistant to all antibiotics tested. Most isolates belong to the circulating IC2 clonal type. SNP analysis revealed four potential outbreak clusters. Two of these clusters showed high concordance with the local spatio-temporal epidemiology, suggesting that transmission events were very likely. Conclusions: Our data suggest that there were two independent transmission events, which would have been missed by conventional MLST owing to high clonality. The routine implementation of WGS can optimize surveillance and initiation of suitable containment measures. In addition, emerging resistance to salvage therapy is a major therapeutic problem and should be monitored closely.